Impact of Subsidy Removal on Mathematics Education in Nigerian Schools - Olaoye Abiodun Emmanuel; Onoge Honmane (Research Parks Publishing LLC, 2023)
This paper assessed the impact of subsidy removal on mathematics education in Taraba state. Secondary data were used in the paper. The data were collected from print and online publications. The paper concluded that subsidy removal in Nigeria has affected implementation of mathematics education in Taraba state and affected supervision of mathematics education. It has also led to increment in the prices of instructional materials of mathematics. Based on this, the paper recommended that government should increase the funding of education and increase salaries and allowances of mathematics teachers. Government should increase budgetary allocation for the supervision of mathematics programme and subsidize the prices of mathematics instructional materials.